What Goes Around, Comes Around - HSV-1 Replication in Monocyte-Derived Dendritic Cells - Grosche, Linda; Kummer, Mirko; Steinkasserer, Alexander (Frontiers in Microbiology, 2017)
HSV-1 is a very successful human pathogen, known for its high sero-prevalence and the ability to infect a wide range of different cell types, including dendritic cells (DCs). As very potent antigen-presenting cells DCs play an important role in the induction of antiviral immune responses and therefore represent a strategic target for viral-mediated immune escape mechanisms. It is known that HSV-1 completes its gene expression profile in immature as well as in mature DCs, while lytic infection is only found in immature DCs (iDCs). Notably, HSV-1 infected mature DCs (mDCs) fail to release infectious progeny virions into the supernatant. Apart from HSV-1 dissemination via extracellular routes cell-to-cell spread counteracts a yet unknown mechanism by which the virus is trapped in mDCs and not released into the supernatant. The dissemination in a cell-cell contact-dependent manner enables HSV-1 to infect bystander cells without the exposure toward the extracellular environment. This supports the virus to successfully infect the host and establish latency. In this review the mechanism of HSV-1 replication in iDCs and mDCs and its immunological as well as virological implications, will be discussed.
EVALuna2:36216